2016
DOI: 10.11646/phytotaxa.288.3.4
|View full text |Cite
|
Sign up to set email alerts
|

Pterocladiella maribagoensis (Gelidiales, Rhodophyta), a new marine alga from Cebu, Philippines

Abstract: A new species of marine gelidioid red algae, Pterocladiella maribagoensis, is described and illustrated. Pterocladiella maribagoensis is distinguished by small, terete to compressed thalli with alternate or irregular branches, peg-like haptera, rhizines in medulla, and tetrasporangial sori without sterile margin at the terminal of branches. Analyses of both mitochondrial cox1 and plastid rbcL sequences revealed that P. maribagoensis was distinct from other species of Pterocladiella and clustered with P. austra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Pterocladiella was established on the basis of four species, previously placed in the genus Pterocladia J.Agardh; the generitype is P. capillacea (S.G.Gmelin) Santelices & Hommersand ( Santelices and Hommersand, 1997 ). To date, 24 species have been described, many using morphological characters in combination with molecular markers ( Shimada et al, 2000 ; Thomas and Freshwater, 2001 ; Tronchin and Freshwater, 2007 ; Freshwater et al, 2010 ; Sohrabipour et al, 2013 ; Boo and Geraldino, 2016 ; Boo et al, 2016a , 2016b , 2017 ; Iha et al, 2017 ; Wang et al, 2020 ). Boo et al (2017) found that P. caloglossoides (M.Howe) Santelices from Peru, the type locality, was distantly related to the Australian taxa identified by Millar and Freshwater (2005) , indicating that specimens from other regions (e.g., China, Hawai’i, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Pterocladiella was established on the basis of four species, previously placed in the genus Pterocladia J.Agardh; the generitype is P. capillacea (S.G.Gmelin) Santelices & Hommersand ( Santelices and Hommersand, 1997 ). To date, 24 species have been described, many using morphological characters in combination with molecular markers ( Shimada et al, 2000 ; Thomas and Freshwater, 2001 ; Tronchin and Freshwater, 2007 ; Freshwater et al, 2010 ; Sohrabipour et al, 2013 ; Boo and Geraldino, 2016 ; Boo et al, 2016a , 2016b , 2017 ; Iha et al, 2017 ; Wang et al, 2020 ). Boo et al (2017) found that P. caloglossoides (M.Howe) Santelices from Peru, the type locality, was distantly related to the Australian taxa identified by Millar and Freshwater (2005) , indicating that specimens from other regions (e.g., China, Hawai’i, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Pterocladiella represents a good example in this regard, taking into account the difficulty of studying small taxa growing in dense turf communities, which hide a variety of so far overlooked diversity [ 15 , 16 , 17 ]. Phylogenetic analyses using several molecular markers individually and in various combinations have proven to be very useful tools for establishing the differences and similarities among species not detected by morphological studies [ 1 , 2 , 14 , 39 ]. After the recent results presented by Boo et al [ 19 ], Pterocladiella joins a growing list of red algal taxa such as Lithophyllum Philippi [ 40 ], Portieria Zanardini [ 41 ], Polysiphonia Greville [ 42 ], Porolithon Foslie [ 43 ], or Sporolithon Heydrich [ 44 ] for which DNA sequence analyses have resulted in a remarkable increase in species diversity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the type species, Pterocladiella capillacea (Gmelin) Santelices and Hommersand, three other species were assigned to the new genus supported by both morphological and molecular evidence [ 5 , 6 ]. Subsequent studies led to the transfer of a total of ten species initially assigned to Pterocladia within Pterocladiella [ 7 , 8 , 9 ], and uncovered an ensemble of new species based on molecular and morphological datasets, mainly among small taxa with relatively simple morphologies growing in dense turf-like communities [ 1 , 2 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Currently, a total of 25 species with warm-temperate to tropical distributions are accepted in Pterocladiella [ 18 ].…”
Section: Introductionmentioning
confidence: 99%